Predictive ADMET : integrative approaches in drug discovery and development - Wang, Jianling, 1958-; Urban, Laszlo, 1951- (Hoboken, New Jersey : Wiley, 2014)
"By guiding in the application of techniques and tools for predicting ADMET outcomes in drug candidates, Predictive ADMET offers a road map for drug discovery scientists to generate effective and safe drugs for unmet medical needs. Featuring case studies and lessons learned from real drug discovery and development, the text: helps users diagnose ADMET problems; presents appropriate recommendations; introduces the current clinical practice for drug discovery and development; and consolidates the tools and models to intelligently integrate existing in silico, in vitro and in vivo ADMET data"--Provided by publisher.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Drug development -- Methodology; Drug Discovery -- methods; Pharmacokinetics; MEDICAL -- Pharmacology; Electronic books; Electronic books